Efisiensi Generator Set Terhadap Perubahan Beban Listrik Pada Kapal Perikanan - Prasetyo, Djoko; Nurfauzi, Akhmad; Abrori, M. Zaki Latif (Edu Elektrika Journal, 2021)
Abstract— Electrical energy on fishing vessels is an unavoidable energy requirement, the electric source on board is obtained from an electric generator which is generally driven by a diesel engine. Electrical energy on fishing vessel is used for lighting, navigation purposes and assisting fishing activities to loading and unloading. The electric generator on fishing vessel will operate properly and have a long service life if the load applied to the generator does not exceed the load factor limit. Researchers carried out several stages, i.e: identify the electric power distribution system, identify the generator capacity and electrical load received, calculate the electrical load on different operational conditions. In this study, it is also known that the operating efficiency of the generator under four different operational conditions. The results of the research, this fishing vessel uses a radial electrical distribution system; using two units of electric generator with identical specifications, each has a capacity of 225 kVA; the generator operates efficiently in all operational conditions with a load factor of 79.70% to 83.08%.